A DFT study of H2S adsorption and sensing on Ti, V, Cr and Sc doped graphene surfaces - Tunali, omer Faruk; Yuksel, Numan; Gece, Gokhan; Fellah, M. Ferdi (Springer/Plenum Publishers, 2024)
Finding cost-effective and sustainable methods for the removal of hydrogen sulfide (H2S), a highly toxic gas released as a byproduct in many industrial activities, is crucial for environmental health. In this study, the adsorption and electronic sensor properties of Ti, V, Cr and Sc doped graphene nanosheets (GN) for H2S molecule have been investigated using Density Functional Theory (DFT) method. The WB97XD method with 6-31G(d,p)/LanL2DZ basis sets have been utilized in DFT calculations. The charge distribution indicates that the charge transfer occurred between metal doped graphenes and H2S. DFT calculations of H2S molecule adsorption on Ti, V, Cr and Sc doped graphenes demonstrate that the ability to adsorb H2S molecule. The obtained adsorption energy (triangle E) values vary in the range of -54.4 to -71.0 kJ/mol. Furthermore, the electrical conductivity of the Cr doped graphene nanosheet (Cr-GN) changed due to the change in the HOMO-LUMO gap (triangle E-g = 24.8 kJ/mol). This result indicates that the Cr-GN structure is a potential candidate as an electronic sensor for H2S molecule at room temperature. Through methods like DFT, which are cost-effective and highly compatible with experimental results, predicting suitable adsorbents, understanding their properties, and enhancing them are expected to make substantial contributions to the industrial-scale production of these materials in terms of cost and accuracy in the future.
Keywords: DFT; Graphene; Metal doping; Hydrogen sulfide; Adsorption; Sensor